Criminal liability for violation of copyright on social networks - ÇAKIR, KERİM (My University, 2022)
One of the most common and criminal acts on social networks is copyright infringement regarding intellectual property. Reproduction and distribution of copyrighted works over the internet is faster and easier. If a video, picture, photo or original article qualifying as a (piece of) work is shared on social networks without the permission of the author or without attribution, copyright is violated according to intellectual property law.The increasing importance of social networks has led to an increase in copyright infringements in these channels. Since it is very easy to publish and reproduce the work on the internet, Article 71 of the Law on Intellectual and Artistic Works numbered 5846 (“FSEK”) is of great importance in the fight against copyright infringements committed on social networks. This Article regulates the unauthorized use of copyrighted works as a crime and provides for sanctions. Except as permitted by law, a person who reproduces, distributes or makes a work public without the consent of the right holder shall be punished. The norms under Article 71 of FSEK on the protection of copyright belong to the substantive part of criminal law. Although social networks have their own sanctions and preventive measures for copyright infringements, the author must be protected by means of criminal law.In this study, the acts of duplicating, distribution, publicizing, processing, creating a work and giving a link on social networks will be evaluated in accordance with FSEK within the scope of copyright and how to determine the criminal responsibility in case of infringement will be explained. In addition, information will be given about how works benefiting from copyright protection are subject to infringements on social networks, under what conditions these infringements constitute a crime, what kind of legal remedies can be resorted to by the author, how social network service providers make regulations on this issue and the precautions to be taken regarding infringements.

Sosyal ağlarda sıklıkla rastlanan ve suç teşkil eden fiillerden biri de fikri mülkiyete ilişkin telif hakkı ihlalleridir. Telif hakkıyla korunan eserlerin internet üzerinden çoğaltılması ve dağıtılması daha hızlı ve daha kolaydır. Eser niteliğini haiz bir video, resim, fotoğraf veya özgün bir yazı sosyal ağlarda eser sahibinin izni olmaksızın ya da esere atıf yapılmaksızın paylaşılırsa fikri mülkiyet hukukuna göre telif hakkı ihlal edilmiş olur.Sosyal ağların öneminin her geçen gün artması bu mecralarda telif hakkı ihlallerinin de artmasına neden olmuştur. İnternet ortamında eserin yayımlanması ve çoğaltılması oldukça kolay olduğundan FSEK’in 71’inci maddesi sosyal ağlarda işlenen telif hakkı ihlalleriyle mücadelede büyük önem taşımaktadır. Madde, telif hakkıyla korunan eserlerin yetkisiz kullanımını suç olarak düzenlemiş ve yaptırım öngörmüştür. Kanunların izin verdiği haller dışında, hak sahibinin rızası olmaksızın bir eseri çoğaltan, dağıtan veya alenileştiren kişi cezalandırılır. Telif hakkının korunmasıyla ilgili FSEK’in 71’inci maddesindeki normlar ceza hukukunun maddi kısmına aittir. Sosyal ağların, telif hakkı ihlallerine yönelik kendi yaptırım ve engellemeleri söz konusu olsa da eser sahibinin ceza hukuku marifetiyle korunması gerekir.Çalışmada, sosyal ağlarda bir eseri çoğaltma, yayma, kamuya iletme, işleme eser oluşturma ve link verme şeklindeki fiiller, telif hakkı kapsamında 5846 sayılı Fikir ve Sanat Eserleri Kanunu’na göre değerlendirilecek ve ihlal halinde ceza sorumluluğunun nasıl tespit edileceği açıklanacaktır. Ayrıca telif hakkı korumasından faydalanan eserlerin sosyal ağlarda nasıl ihlale konu olduğu, bu ihlallerin hangi şartlar altında suç teşkil ettiği, eser sahibinin ne tür hukuki yollara başvurabileceği, sosyal ağ hizmet sağlayıcılarının bu konuda nasıl düzenleme yaptığı ve ihlallerle ilgili alınması gereken önlemler konusunda bilgi verilecektir.
Sosyal ağlarda telif hakkının ihlali halinde ceza sorumluluğu
Keywords: Copyright; Work; Social Network; Internet Environment; Content Sharing